Peran kepala sekolah dan madrasah sebagai supervisor pada pengembangan kurikulum sekolah pusat keunggulan SMK negeri 1 bagor - Rizky Firdausi (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2025)
The principal is the spearhead of the leadership of an educational institution, both general education and Islamic education. Institutional leaders must have academic, social and personality qualifications and competencies as the basis for becoming a quality leader. The quality of educational institutions, one of which is seen from the role of school principals in various fields. The purpose of this study is to analyze and describe the Role of School Principals and Madrasah in the development of the Curriculum in educational institutions, especially at SMKN 1 Bakor, Nganjuk Regency. This research uses a qualitative approach through field studies. The data collection technique uses interview and documentation methods with data sources obtained through the Principal and the Curriculum Waka. Curriculum is an educational plan and design that will be carried out in an educational institution, both general education and Islamic education. The development of the curriculum at SMK Negeri 1 Bagor, as a Center of Excellence school, cannot be separated from the role of the principal. As a supervisor and controller, the principal plays an important role in curriculum development to improve the quality of the educational institution in accordance with its vision and mission.